Tibetan *-as > -os - Hill, Nathan (My University, 2016)
Both Jacques (2010) and Zeisler (2015) propose explanations for the synchronically unexpected past zos of the Tibetan verb 'eat'. After evaluating their proposals, this essay suggests that zos is the regular outcome of a sound change *as > -os, the results of which were erased through analogy in almost all other verbs.
PUBLISHED
Keywords: Tibetan; Historical linguistics